2020
DOI: 10.3897/zookeys.929.50240
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships and population genetics of the Afrotropical leaf-nosed bats (Chiroptera, Hipposideridae)

Abstract: The Old World leaf-nosed bats (Hipposideridae) are aerial and gleaning insectivores that occur throughout the Paleotropics. Both their taxonomic and phylogenetic histories are confused. Until recently, the family included genera now allocated to the Rhinonycteridae and was recognized as a subfamily of Rhinolophidae. Evidence that Hipposideridae diverged from both Rhinolophidae and Rhinonycteridae in the Eocene confirmed their family rank, but their intrafamilial relationships remain poorly resolved. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 85 publications
(96 reference statements)
2
26
0
Order By: Relevance
“…The former study also showed the endemic West African H. lamottei from Mount Nimba to belong within lineage B, which represents another challenge to the taxonomy of H. caffer complex. Further complexity in the cryptic diversity in H. ruber has been shown by Patterson et al (2020). Although their phylogeny corroborates the basic division into the four main lineages by Vallo et al (2008), several new sublineages were newly introduced from East Africa and together with older redefined sublineages proposed as putative species.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…The former study also showed the endemic West African H. lamottei from Mount Nimba to belong within lineage B, which represents another challenge to the taxonomy of H. caffer complex. Further complexity in the cryptic diversity in H. ruber has been shown by Patterson et al (2020). Although their phylogeny corroborates the basic division into the four main lineages by Vallo et al (2008), several new sublineages were newly introduced from East Africa and together with older redefined sublineages proposed as putative species.…”
Section: Introductionmentioning
confidence: 74%
“…Aligned cytb sequences were first shortened to the length of the shortest sequence and then narrowed down to haplotypes using DnaSP 5.10 (Librado & Rozas, 2009). For assignment of the Ghanaian bats into the major mtDNA lineages A, B, C, and D and for comparison with published data from other African regions, their haplotypes were aligned with selected published haplotypes of H. caffer complex by Vallo et al (2008Vallo et al ( , 2011 and Patterson et al (2020), and outgroup taxa H. jonesi and R. landeri (Figure 2, Table S2, Alignment S1).…”
Section: Identification Of Mtdna Lineagesmentioning
confidence: 99%
See 3 more Smart Citations